Firm Dynamism and Productivity - Patrick Condon; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2021)
A functioning business environment, where labour and capital resources are efficiently reallocated to the most productive activities, is crucial for long-run aggregate productivity growth The COVID-19 pandemic has impacted every aspect of the economy, including the birth, survival and death rates of enterprises, which will have implications for the future competitiveness of the Irish economy Appropriate policies are required to support enterprises through the whole life cycle, from start-up, through the growth phase, to closure Further research and analysis is needed in Ireland to better understand the underlying determinants of enterprises' entry and exit decisions and support enterprise churn rates to boost productivity growth.
Keywords: 330